Illegal grain market in Ukraine: Harvesting war opportunities - Tetiana Melnychuk (Journal of Economic Criminology)
Based on empirical evidence, this research: highlights the timeline of changes in Ukrainian agricultural sector since the onset of the full-scale war in 2022 and the maritime blockade affecting exports; examines the relevant transformation of the illegal grain market amid these extraordinary turbulent circumstances; describes the key components of the heterogeneous illegal grain market, which includes the export of ''black'' grain through the grain corridor and trade in grain as a looted commodity from the occupied territories; identifies the role of organized crime and corruption in illegal transactions of wartime, considering the pre-existing models of the shadow economy functioning. The findings of this research may serve as a theoretical and methodological framework for studying scenarios of illicit economies in the context of armed conflicts and other systemic crises at both national and transnational levels.